Can Soil Compaction Alter Morphophysiological Responses and Soybean Yield under Application of Selective Herbicides? - Bruno César Silva Pereira; Camila Jorge Bernabé Ferreira; Guilherme Braga Pereira Braz; Matheus de Freitas Souza; Rose Luiza Moraes Tavares; Márcio Rosa; Eduardo Lima do Carmo; Gabriel Henrique Vian; Ana Paula Sousa Silva; Fellipe Goulart Machado (Applied and Environmental Soil Science)
Compacted soils may be negatively affecting the selectivity of herbicides applied in preemergence in the soybean crop. Therefore, the present work aimed to investigate possible negative effects on the morphophysiological characters of soybean plants, as well as on the agronomic and yield performances of this crop. For this purpose, two trials were carried out, one in a greenhouse and the other under field conditions. In a greenhouse, the study was carried out in a completely randomized design in a 2 × 8 factorial, with five replications, while in the field, the design used was randomized blocks, with the treatments arranged in split-plot (2 × 8), with six repetitions. The first factor/plot corresponded to the physical condition of the soil: compacted or not compacted, while the second factor/subplot was constituted by the application of preemergence herbicides: clomazone, diclosulam, flumioxazin, S-metolachlor, [imazethapyr + flumioxazin], [pyroxasulfone + flumioxazin], and [sulfentrazone + diuron], plus a control without herbicide. In the greenhouse study, there was a significant interaction between soil compaction and herbicides applied in preemergence for the relative index of chlorophyll b and root dry mass. Furthermore, the isolated herbicide factor did not promote significant changes in any of the morphophysiological variables evaluated. Compaction alone had a negative impact on the variables relative index of chlorophyll a and carbon assimilation rate, with reductions in the values of these variables when the soybean was submitted to growth in compacted soil. For the field experiment, there were no significant interactions between the factors for any of the analyzed variables, nor the effect of herbicides alone. The isolated soil compaction factor negatively impacted the plant stand and the thousand-grain mass of soybean, showing reductions in the values of this parameter when the soybean was grown in compacted soil.